Application of the Self-Assembling Peptide Hydrogel RADA16 for Hemostasis during Tonsillectomy: A Feasibility Study - Joshua Michaels; Anna I. Kaleva; Laura Bateman; Oliver Wakelam; Joanna Stephens (Journal of Functional Biomaterials, 2024)
Tonsillectomy is a common surgical procedure but carries a high risk of readmission for secondary bleeding and pain. This study evaluated the feasibility and effectiveness of using the hemostatic self-assembling peptide hydrogel RADA16 (PuraBond, 3-D Matrix SAS; Caluire et Cuire, France) to control bleeding from the tonsillectomy wound bed. Readmission/re-operation rates were compared between a prospective case series of 21 primarily adult tonsillectomy patients treated with topical RADA16 and an untreated historical Control group of 164 patients who underwent tonsillectomy by 10 surgeons at a single tertiary hospital in the UK between March 2019 and June 2022. Cumulative readmission rates for any reason were 2-fold elevated in Control subjects (18.9%; n = 31/164 subjects) compared to patients treated intra-operatively with RADA16 hemostatic hydrogel (9.5%; n = 2/21) (p = 0.378). Readmission rates for postoperative bleeding were 3-fold higher in Controls (14.6%; n = 24/164 subjects) than in the RADA16-treated group (4.8%; n = 1/21) (p = 0.317). A similar rate of retreatment for pain was recorded in the Control (4.3%; n = 7/164) and RADA16 (4.8%; n = 1/21) groups (p = 0.999). Two Control subjects (1.2%) required re-operation for recalcitrant bleeding; no RADA16 subject (0.0%) required re-operation for any reason. No device-related adverse events occurred in the RADA16 group. Surgeons were pleased with the easy learning curve and technical feasibility associated with intra-operatively administering RADA16 hemostatic hydrogel. Intra-operative hemostasis using RADA16 peptide hydrogel was straightforward and was associated with a trend of 3-fold lower rates of readmission for postoperative bleeding events than untreated Control subjects.